2022
DOI: 10.1038/s41467-022-31817-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NMDA receptors through a membrane-to-channel path

Abstract: N-methyl-d-aspartate receptors (NMDARs) are transmembrane proteins that are activated by the neurotransmitter glutamate and are found at most excitatory vertebrate synapses. NMDAR channel blockers, an antagonist class of broad pharmacological and clinical significance, inhibit by occluding the NMDAR ion channel. A vast literature demonstrates that NMDAR channel blockers, including MK-801, phencyclidine, ketamine, and the Alzheimer’s disease drug memantine, can bind and unbind only when the NMDAR channel is ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…4G,H) and 100 µM memantine (Glasgow et al, 2018; Kolcheva et al, 2021). Recent data have shown that the GluN2A-M630 amino acid residue lines the fenestration of memantine via MCI (Wilcox et al, 2022). Therefore, we next assessed whether GluN1/GluN2A receptors with the mutated GluN2A-M630 residue exhibit altered MCI induced by K2060 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4G,H) and 100 µM memantine (Glasgow et al, 2018; Kolcheva et al, 2021). Recent data have shown that the GluN2A-M630 amino acid residue lines the fenestration of memantine via MCI (Wilcox et al, 2022). Therefore, we next assessed whether GluN1/GluN2A receptors with the mutated GluN2A-M630 residue exhibit altered MCI induced by K2060 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we observed a decrease in τ slow and A slow in the presence of Mg 2+ , which may also be attributable to the reduction of MCI induced by K2060 in the presence of Mg 2+ . In the case of memantine, MCI was explained by the presence of a fraction of the uncharged form that interacts with the membrane and then fenestrates into the ion channel of the GluN1/GluN2 receptor (Wilcox et al, 2022). The stronger MCI of K2060 may be explained by differential lipophilicity (memantine clogP = 2.07; MK-801 clogP = 3.31; K2060 clogP = 4.59; MarvinSketch software v. 23.8; estimated values), although both memantine and K2060 are likely to wash off the membrane in the order of seconds (Kotermanski and Johnson, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The memantine/perampanel CLD-GA paradigm that is effective against CPZ-induced white matter injury was based on doses an order of magnitude below the clinical treatment range for these drugs and is an attractive alternative to full-dose co-administration such as that tested in stage II clinical trials for glioblastoma (eg., 34 ). Membrane-to-channel inhibition has recently been described for lipophilic antagonists of NMDA and AMPA receptors, which can diffuse from the cell membrane into the receptor protein via gated fenestration 35,36 . To take advantage of this phenomena and further extend the clinical potential of the CLD approach, we tested a combination of two experimental antagonists that are structural analogues of myelin-targeting fluorescent dyes.…”
Section: New Ex Vivo Models Of Acute Demyelinationmentioning
confidence: 99%
“…Fenestrations in the pore walls are observed in all available structures and density consistent with a lipid is present in both agonist-free and fructose-bound BmGr9 structures, suggesting that the lipids form part of a stable pore structure. Fenestrations opening the ion path to the membrane environment have been observed in several other ion channel families, including ionotropic glutamate receptors, cys-loop receptors, voltage-gated potassium channels and sodium channels, and mechanosensitive two-pore domain potassium (K2P) channels [35][36][37][38][39] . In some channels, such fenestrations are transient, while in others they are observed in both closed and open channel states.…”
Section: Pore-penetrating Lipids As a Common Feature Of Grs And Orsmentioning
confidence: 99%